Evidence-based management of lipid disorders - Vissers, Maud N.; Kastelein, John J. P.; Stroes, Erik S. (TFM, 2010)
Focuses on clinical issues that are associated with the management of lipid disorders. This book includes such topics as therapeutic strategies for managing hereditary lipid disorders, including familial hypercholesterolaemia, both in adults and children, and familial combined hypercholesterolaemia